Teachers’ Acceptance of Google Sites for Ecosystem Learning: Keberterimaan Guru terhadap Google Sites untuk Pembelajaran Ekosistem - Arina, Ida; Abidin, Yunus; Kurniawan, Dede Trie (Indonesian Journal of Innovation Studies, 2025)
Background (General): Digital platforms are increasingly adopted in elementary education to address challenges in student engagement. Background (Specific): In ecosystem learning within science education, conventional methods often fail to sustain motivation and active participation. Google Sites offers an alternative as an interactive and accessible tool for teaching. Knowledge Gap: Few studies in Indonesia have examined teachers’ acceptance of Google Sites for elementary-level ecosystem learning using a structured theoretical framework. Aim: This study analyzes teachers’ acceptance of Google Sites by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Results: Findings show that all measurement indicators met validity and reliability criteria, with factor loadings above 0.7, composite reliability exceeding 0.7, and AVE values above 0.5. Teachers reported Google Sites as useful, easy to use, supported socially, and adequately facilitated by resources. Novelty: This study provides the first structured UTAUT-based evaluation of Google Sites in Indonesian elementary science education. Implications: Results suggest that Google Sites can support teachers in designing more meaningful and interactive ecosystem learning, offering practical insights for integrating digital media in schools. Highlight Teachers accepted Google Sites positively in ecosystem learning. All validity and reliability indicators met recommended standards. Google Sites supports engaging and meaningful classroom experiences. Keyword UTAUT, Google Sites, Ecosystem Learning, Elementary Education, Teacher Acceptance